Robots trends and megatrends: artificial intelligence and the society - Molfino, Rezia; Cepolina, Francesco E.; Cepolina, Emanuela; Cepolina, Elvezia Maria; Cepolina, Sara (Industrial robot, 2024)
PurposeThe purpose of this study is to analyze the robot trends of the next generation.Design/methodology/approachThis paper is divided into two sections: the key modern technology on which Europe's robotics industry has built its foundation is described. Then, the next key megatrends were analyzed.FindingsArtificial intelligence (AI) and robotics are technologies of major importance for the development of humanity. This time is mature for the evolution of industrial and service robots. The perception of robot use has changed from threading to aiding. The cost of mass production of technological devices is decreasing, while a rich set of enabling technologies is under development. Soft mechanisms, 5G and AI have enabled us to address a wide range of new problems. Ethics should guide human behavior in addressing this newly available powerful technology in the right direction.Originality/valueThe paper describes the impact of new technology, such as AI and soft robotics. The world of work must react quickly to these epochal changes to enjoy their full benefits.